IMPLEMENTATION OF CONFLICT MANAGEMENT IN IMPROVING THE PERFORMANCE OF PRIVATE ISLAMIC RELIGIOUS UNIVERSITIES IN LAMPUNG - Siti Patimah; Yuyun Yunita; Safriadi Safriadi (Pascasarjana IAIN Metro, 2022)
The goal of conflict management is to achieve optimal performance quality by maintaining functional conflicts and minimizing the consequences of adverse conflicts. Conflict management is useful in achieving the goals being fought for and maintaining good relations between the parties involved in the conflict. The essence of the conflict is one of them because of global competition. The core of global competition is competition for human resources or the shift from comparative advantage to competitive advantage. This type of research is a qualitative research, using the methods of observation, interviews and documentation in collecting data in the field. This research will reveal and explain the various meanings of concepts or phenomena of experience based on the awareness that occurs in some participants naturally so that efforts to understand the various phenomena that occur can run optimally. This research is descriptive, aims to obtain in-depth information. Based on the exposure in the discussion and analysis carried out, it can be concluded that it cannot be generalized implicitly that conflict is something that is detrimental or beneficial. In order for conflict to improve the performance and productivity of an organization, the leadership of the organization is required to have the ability to manage conflict. There are several conflict control techniques in all situations, each of which has advantages and disadvantages. Conflicts need to be resolved in an appropriate and appropriate way against the background of the conflict. The causes of conflict are not solely internal to the organization but also external to the organization.